ENVIRONMENTAL ENRICHMENT AND BEHAVIOUR OF PIGS: REVIEW - Foppa, L.; Caldara, F. R.; Machado, S.P.; Moura, R.; Santos, R. K. S.; Nääs, I. A.; Garcia, R. G. (Revista Brasileira de Engenharia de Biossistemas, 2014)
There is a great concern in the scientific community and the consumer market over the methods that animals are produced. The new demands of the external market, in relation to the ethical quality of the products available to the consumer, require new techniques directed to animal welfare. In industrial pig farming, animals usually live confined in all stages of life. Therefore, studies are being conducted to minimize the effects of stress generated by the confinement environmental. The use of objects for environmental enrichment may be a viable alternative for adaptation of Brazilian swine production. However, its efficacy is still limited due to rapid habituation of pigs to objects provided. The aim of this paper is to review alternatives for environmental enrichment used in pig farming.